Ikaw ay akin - Bernal, Ishmael; Carreon, Jose N.; Lobo, Sergio; Salvador, Augusto; Aunor, Nora.; Santos, Vilma; De Leon, Christopher; Romano, Nick.; Andolong, Andrea; Zarate, Ernie ([Metro Manila] Tagalog Ilang-Ilang Productions, 1978)
Rex and Tere have been together for five years. They have a peaceful relationship until Rex met Sandra, a designer. Rex and Tere's relationship became chaotic ; and Rex can't decide whom to choose between the two women.
Director, Ishmael Bernal ; story, Ishmael Bernal ; screenplay, Jose N. Carreon ; director of photography, Sergio Lobo ; editing, Augusto Salvador.
Nora Aunor, Vilma Santos, Christopher de Leon, Nick Romano, Andrea Andolong, Ellen Esguerra, Odette Khan, Zandro Zamora, Ven Medina, Angel Confiado, Renato Requiestas, Ernie Zarate.
Keywords: Triangles (Interpersonal relations) -- Philippines -- Drama